Recent Advances in Rice Research - Rahman Ansari, Mahmood-ur- (IntechOpen, 2021)
"Recent Advances in Rice Research" is an interdisciplinary book dealing with diverse topics related to recent developments in rice research. The book discusses the latest research activities in the field of hybrid rice, various metabolites produced in rice and its biology, stress studies, and strategies to combat various biotic and abiotic stresses as well as rice economics, value addition, and product development. The book is written by an international team of researchers from all over the globe sharing their results in the field of rice research. I am hopeful that the scientific information available in this book will provide advanced knowledge for rice researchers, students, life scientists, and interested readers on some of the latest developments in rice research.